How "Pharmacoresistant" is Cav2.3, the Major Component of Voltage-Gated R-type Ca2+ Channels? - Jürgen Hescheler; Maxine Dibué; Toni Schneider (MDPI AG, 2013)
Membrane-bound voltage-gated Ca2+ channels (VGCCs) are targets for specific signaling complexes, which regulate important processes like gene expression, neurotransmitter release and neuronal excitability. It is becoming increasingly evident that the so called "resistant" (R-type) VGCC Cav2.3 is critical in several physiologic and pathophysiologic processes in the central nervous system, vascular system and in endocrine systems. However its eponymous attribute of pharmacologic inertness initially made in depth investigation of the channel difficult. Although the identification of SNX-482 as a fairly specific inhibitor of Cav2.3 in the nanomolar range has enabled insights into the channels properties, availability of other pharmacologic modulators of Cav2.3 with different chemical, physical and biological properties are of great importance for future investigations. Therefore the literature was screened systematically for molecules that modulate Cav2.3 VGCCs.